Immediate implants with buccal defects filled with bone from the tuberosity or a xenograft: 1-year randomized trial - Gonzalo Stagnaro BORGIA; Pablo PEBÉ; Roberto BARBOT; Alex Nogueira HAAS (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract The aim of this study was to compare the use of autologous bone from tuberosity (TUBER) and deproteinized bovine bone mineral (DBBM) in immediate implants with buccal bone defects. A total of 31 patients with one single tooth in the upper anterior region indicated for extraction presenting tomographic buccal bone defect were analyzed. Immediate implantation was conducted for all patients. In one group, DBBM and a collagen membrane were inserted into the buccal defect; in the other group, a small block of bone from tuberosity was used. The primary outcome was facial-palatal ridge thickness (FPT) measured in casts 1 year after function. The implant success rate was 100% in both groups. FPT changes were <0.5 mm and did not differ significantly between groups. FPT reductions in the DBBM and TUBER groups were 1% and 0.6%, respectively, at the gingival margin and 5% and 2%, respectively, at 6 mm apical of the gingival margin (p > 0.05). No significant differences were observed between groups for patient's esthetic, satisfaction, pain and quality of life. Pink esthetic scores for the DBBM and TUBER were 11.5±1.7 and 10.8±1.9, respectively (p=0.37). It can be concluded that DBBM and TUBER did not differ in terms of ridge alterations, peri-implant clinical parameters and patient-reported outcomes.